Metformin improves renal injury of MRL/lpr lupus-prone mice via the AMPK/STAT3 pathway - Chen, Xiao-cui; Wu, Dan; Wu, Hong-luan; Li, Hui-yuan; Yang, Chen; Su, Hong-yong; Liu, Ze-jian; Huang, Xiao-rong; Lu, Xing; Huang, Li-feng; Zhu, Shao-ping; Pan, Qing-jun; et al. (Lupus science & medicine, 2022)
ObjectiveLupus nephritis (LN) is a major complication and cause of death among patients with SLE. This research used in vivo and in vitro experiments to explore the therapeutic potential of metformin in kidney injury from LN-induced inflammation.MethodsIn vivo study, 8-week-old MRL/MpJ-Faslpr/J (MRL/lpr) mice were randomly divided into two groups (n=12 each): daily administration of 0.3 mg/mL metformin in drinking water and control (water only). Body weight and urinary samples were measured biweekly. Mice were sacrificed after 8-week treatment to harvest serum, lymph nodes, spleen and kidneys. In vitro study, human kidney-2 (HK-2) cells were pretreated with 1 mM metformin for 1 hour and then stimulated with 20 µg/mL lipopolysaccharides (LPS) or 10 ng/mL tumour necrosis factor-α (TNF-α) for another 48 hours. Protein was collected for subsequent analysis.ResultsWe found that metformin administration improved renal function in MRL/lpr lupus-prone mice, measured by decreased urea nitrogen and urinary proteins. Metformin reduced immunoglobulin G and complement C3 deposition in glomeruli. The treatment also downregulated systemic and renal inflammation, as seen in decreased renal infiltration of F4/80-positive macrophages and reduced splenic and renal MCP-1 (monocyte chemoattractant protein-1) and TNF-α, and renal IL-1β (interleukin 1β) expression. Metformin administration decreased renal expression of necroptosis markers p-RIPK1 (phosphorylated receptor-interacting protein kinase 1) and p-MLKL, along with tubular injury marker KIM-1 (kidney injury molecule-1) in lupus mice. In addition, metformin alleviated the necroptosis of HK-2 cells stimulated by LPS and TNF-α, evidencing by a decrease in the expression of necroptosis markers p-RIPK1, p-RIPK3 and p-MLKL, and the inflammasome-related markers NLRP3 (NLR family pyrin domain containing 3), ASC (apoptosis-associated speck-like protein containing a CARD), caspase-1. Mechanistically, metformin treatment upregulated p-AMPK (phosphorylated AMP-activated protein kinase) and downregulated p-STAT3 (phosphorylated signal transducer and activator of transcription 3) expression in the kidneys. Moreover, AMPKα2 knockdown abolished the protective effects of metformin in vitro.ConclusionsMetformin alleviated kidney injury in LN though suppressing renal necroptosis and inflammation via the AMPK/STAT3 pathway.